AB1077 The spread of tophaceous disease strongly predicts time to new flare in gouty arthritis. (23rd January 2014) - Schlesinger, N.; Sunkureddi, P.; Alten, R.; Bardin, T.; Shpilsky, A.; Kiechle, T.; So, A.
Abstract : Background: In gouty arthritis (GA) elevated serum urate (SU) levels lead to the monosodium urate (MSU) crystal deposition (tophi) in cartilage, tendon sheaths, and subcutaneous tissue. This usually appears late in the disease course and indicates disease severity. However, currently there is no quantitative measure to differentiate severe from less severe GA patients using spread of tophaceous disease. Objectives: To develop a quantitative measure of GA severity by the number of tophi locations. Methods: Pooled analysis of two 12-week studies (β-RELIEVED, N=230; β-RELIEVED II, N=226) followed by 12-week extensions, demonstrated a significant reduction in time to new flare in patients treated with canakinumab 150 mg s.c. vs. triamcinolone acetonide (TA) 40 mg i.m. (p<0.0001). Additional retrospective analysis was conducted to explore the impact of the spread of tophaceous disease on time to new flare. A new quantitative measure was derived by summation of tophi locations (right upper limb, left upper limb, right lower limb, left lower limb, and one "other") resulting in a 6-point ordinal measurement scale. Number of tophi locations, using this scale, ranged from 0 to 5. The number of tophi locations was evaluated as a covariate in the Cox regression model using Wald Chi-Square test. Results: The number of tophi locations revealed a high statistical significance along with treatment effect (p<0.0001 for both) i.e. the fewer the number of tophi locations, the longer the time to new flare. A similar result was obtained from Kaplan-Meier (K-M) analysis using log-rank test across the strata of 3 subgroups of tophi category (0, 1-2, 3-5) [Figure]. Conclusions: Our results suggest that the number of locations to which tophaceous formations have spread throughout the body leading to systemic disease is an indicator of disease severity in GA. This quantitative measure is a strong predictor of delay of new flare (the higher the number of locations the less delay in reflares). Disclosure of Interest: N. Schlesinger Grant/Research support from: Novartis, Consultant for: Novartis, URL Pharma, Savient, Takeda, Rx Ensyme, Speakers Bureau: Novartis, P. Sunkureddi Consultant for: Novartis, Bristol Myers Squibb, UCB, Pfizer, Speakers Bureau: Novartis, Bristol Myers Squibb, UCB, Pfizer, R. Alten Grant/Research support from: Novartis, Consultant for: Novartis, Speakers Bureau: Novartis, T. Bardin Grant/Research support from: Menarini, Consultant for: Novartis, Ipsen, Menarini, Ardea, Biocryst, Speakers Bureau: Novartis, A. Shpilsky Shareholder of: Novartis, Employee of: Novartis, T. Kiechle Shareholder of: Novartis, Employee of: Novartis, A. So Grant/Research support from: Novartis, Consultant for: Novartis, Ardea, Speakers Bureau: Novartis, Ardea, Menarini